PENERAPAN MATERIAL KOMPOSIT FIBER REINFORCED POLYMER (FRP) PADA STANG KERUGG RAWIT - Farras Rafi Maulana; Hardy Adiluhung; Yoga Puji Raharjo (Gorga : Jurnal Seni Rupa, 2023)
The automotive sector has developed very rapidly and has contributed to world development both in terms of usability as well as in terms of visuals with the phenomenon of vehicles in various forms. But even automotive developments are directly proportional to the negative impact that has arisen. Correlating with this phenomenon, the government issued a solution by developing electric vehicles which made various parties compete to develop it. One of the parties developing electric vehicles, namely PT Konderatu Artistika, has launched a brand called Kerugg Rawit series. Rawit is an electric motorbike with a unique shape, especially on the handlebar, so it requires materials with high flexibility and strength in the manufacturing process. Fiber Reinforced Polymer (FRP) is a composite material with high flexibility and strength that is suitable for use as the main handlebar material. The use of FRP as the main handlebar material is to simplify the manufacturing process without affecting the quality of the handlebars, especially by adding a raft system to make it easier for the user. By using the User-Centered Design method that focuses on user needs, it is known that FRP can be a solution in making handlebars. Rawit Handlebars with the main material FRP have high durability, light weight, anti-rust and easy to manufacture. The use of FRP composite materials is considered very appropriate as the main material for Kerugg Rawit handlebars.Keywords: electric vehicle, FRP, handlebar. AbstrakSektor otomotif telah berkembang sangat pesat dan telah berkontribusi pada perkembangan dunia baik dari segi kegunaan juga segi visual dengan adanya fenomena kendaraan dengan bentuk yang beragam. Tetapi perkembangan otomotif pun berbanding lurus dengan dampak negatif yang ditimbulkan. Berkorelasi dengan fenomena tersebut pemerintah mengeluarkan solusi dengan mengembangkan kendaraan listrik yang membuat berbagai pihak berlomba untuk mengembangkannya. Salah satu pihak yang mengembangkan kendaraan listrik yaitu PT Konderatu Artistika dengan mengeluarkan sebuah brand bernama Kerugg seri Rawit. Penciptaan ini bertujuan untuk penerapan material komposit Fiber Reinforced Polymer (FRP) pada stang kerugg rawit. Penciptaan ini menggunakan metode perancangan User-Centered Design yang berfokus pada kebutuhan pengguna. Hasil penciptaan diketahui bahwa FRP dapat menjadi solusi dalam pembuatan stang. Stang rawit dengan material utama FRP memiliki daya tahan tinggi, bobot ringan, anti-karat dan mudah dibuat. Penggunaan material komposit FRP dinilai sangat tepat sebagai material utama stang Kerugg Rawit.Kata Kuci: kendaraan listrik, FRP, stang. Authors:Farras Rafi Maulana : Telkom UniversityHardy Adiluhung : Telkom UniversityYoga Puji Raharjo : Telkom University References:Adiluhung, H. (2021). Proses Kreatif Tim Desainer Rancang Bangun Kendaraan Tempur Kelas Ringan PT Pindad. Gorga: Jurnal Seni Rupa, 10(1), 10-14.Chuan, L. B. (2005). Linear Static Finite Element Analysis of Composites Hat-Stiffened Laminated Plates. (Thesis, Universiti Teknologi Malaysia).Clyne, T.W. & Hull, D. (2019).  An introduction to Composite Materials. Cambridge: Cambridge University Press.Kementrian Lingkungan Hidup dan Kehutanan (2021). Uji Emisi Kendaraan sebagai Bentuk Kontribusi Masyarakat terhadap Pengendalian Pencemaran Udara. Jakarta: Kementrian Lingkungan Hidup dan Kehutanan.Kumara, N. S. (2008). Tinjauan perkembangan kendaraan listrik dunia hingga sekarang. Transmisi: Jurnal Ilmiah Teknik Elektro, 10(2), 89“96.Lego, D., Azis, A. C. K., Medan, J. W. I. P. V., & Tuan, P. S. (2022). Ilustrasi T-Shirt Gunnery Artwear. DEKAVE: Jurnal Desain Komunikasi Visual, 12(2), 116-125.Lowdermilk, T. (2013). User-centered Design: A Developer's Guide to Building User-Friendly Applications. Sebastopol: O'Reilly Media, Inc.Mahardika, I. G. N. (2023), œPerkembangan Kenderaan Listrik. Hasil Wawancara Pribadi: 5 Maret 2023, PT Konderatu Artistika.Masuelli, M. (2013). Fiber Reinforced Polymers: The Technology Applied for Concrete Repair. San Lois: Intech Open.Peraturan Presiden Republik Indonesia Nomor 55. (2019). Percepatan Program Kendaraan Bermotor Listrik Berbasis Baterai (Battery Eletric Vehicle) untuk Transportasi Jalan. Jakarta.Tinambunan, N., Triyanto, R., & Azis, A. C. K. Ilustrasi cerpen Renjaya Siahaan pada Koran Analisa. Gorga: Jurnal Seni Rupa, 10(1), 56-61.Yuda, R., Sucipto, F. D., & Ghifari, M. (2022). Perancangan maskot ISBI Aceh sebagai Upaya Penguatan Brand Awareness. Gorga: Jurnal Seni Rupa, 11(1), 36-44.